A Preliminary Assessment of Physical Properties of Sediment at Sembrong Reservoir - Syed Hashim, Syarifah Intan Najla Syed Hashim; Abu Talib, Siti Hidayah; Hj Abustan, Muhammad Salleh (International Journal of Integrated Engineering, 2019)
Reservoir is one of the main sources of water supply and provides functions to hydroelectric power, domestic use, agriculture, flood protection and recreation. Due to the rapid farming, agricultural activities and oil palm trees plantation development that contribute to the increment of sediment, the Sembrong reservoir is slowly endangered due to the shrinkage of reservoir storage. Therefore, this research is initiated to characterize the sediment which could be used as control in future research in the treatment of contaminated sediment. The objective of this study was to determine distribution of physical properties of sediment based on Sembrong Reservoir sediment. In this study, sediment samples were collected using gravity corer at different points in the reservoir area. The physical properties of sediment was investigated by conducted experiments include particle size distribution, bulk density test, moisture content, loss of ignition and scanning electron microscope (SEM). From the data obtained, the bulk density at horizontal distribution was almost the same and the average values obtained was between 10-17 kN/m3. Moisture content of sediment at horizontal distribution at location 3 was the highest with 185.04%. From the particle size distribution, it can be concluded that location 2 had the highest percentage of finer sand where the value was 81% while 19% were silt and clay. For horizontal distribution of organic content, location 5 had the highest result with the percentage of 12.768%. For particle shape of sediment, it was in bulky and flaky categories while the void ratio was getting smaller by the depth.